2001
DOI: 10.1046/j.1365-8711.2001.04172.x
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar structure of RU Lupi down to au scales

Abstract: We have used the technique of spectro-astrometry to study the milli-arcsecond scale structure of the emission lines in the T Tauri star RU Lupi. The wings of the H-alpha emission are found to be displaced from the star towards the south-west (blue wing) and north-east (red wing) with angular scales of 20-30 milli-arcsecs. This structure is consistent with a bipolar outflow from the star. From a study of the variability of the intensity and position spectra we argue that a combination of magnetically-driven bip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
120
5

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 46 publications
24
120
5
Order By: Relevance
“…Our measurements of RU Lup can be simulated equally with an active disk model with or without a dust-free gap. A disk model with a gap was formerly proposed by Takami et al (2001) based on spectro-astrometric observations. viii.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our measurements of RU Lup can be simulated equally with an active disk model with or without a dust-free gap. A disk model with a gap was formerly proposed by Takami et al (2001) based on spectro-astrometric observations. viii.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent lack of redshifted line components results from an obscuration of the dorsal outflow by the circumstellar disk (Eislöffel et al 2000). Takami et al (2001) found that the Hα line in the spectrum of RU Lup, which is evident predominatly in the innermost regions, shows both blueshifted and redshifted wings. This finding is explained by an inner disk gap that allows regions behind the disk to be observed.…”
Section: Ru Lupmentioning
confidence: 97%
See 2 more Smart Citations
“…However, higher spatial resolution is still required to approach the launching region of outflows close to the central star. Recently, new observational efforts such as spectro-astrometry (Takami et al 2001) and long slit spectroscopy with an adaptive optics (Pyo et al 2003(Pyo et al , 2006 have been made to reveal the circumstellar structure of TTSs down to AU scales.…”
Section: Introductionmentioning
confidence: 99%